2019
DOI: 10.2147/idr.s229799
|View full text |Cite
|
Sign up to set email alerts
|

<p>Multi-Drug Resistant <em>Escherichia coli</em> Causing Early-Onset Neonatal Sepsis – a Single Center Experience from China</p>

Abstract: Background and objectiveInfections caused by extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli (E. coli) have raised public-health concerns and are becoming a global health challenge. This study aimed to investigate changes in antimicrobial resistance of E. coli responsible for early-onset sepsis (EOS) in a perinatal center in eastern China.MethodsTwo periods, 2002 to 2008 and 2012 to 2018, were investigated. EOS was defined as the presence of a single potentially pathogenic bacterium grown fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…The incidence of E. coli early-onset sepsis in very low birth weight infants was estimated at 1.04%, reaching a mortality rate of 35.3% (10). A recent meta-analysis based on a systematic review of published studies in the Chinese literature demonstrated that, among the newborn infants hospitalized in Chinese NICUs, ∼50% of all E. coli bloodstream isolates (independently of being early or late onset) were multi-drug resistant due to extendedspectrum beta-lactamase (ESBL) production (11,12). Emerging antibiotic resistance is currently acknowledged as one of the most significant public health problems with high mortality rates associated with multidrug-resistant bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of E. coli early-onset sepsis in very low birth weight infants was estimated at 1.04%, reaching a mortality rate of 35.3% (10). A recent meta-analysis based on a systematic review of published studies in the Chinese literature demonstrated that, among the newborn infants hospitalized in Chinese NICUs, ∼50% of all E. coli bloodstream isolates (independently of being early or late onset) were multi-drug resistant due to extendedspectrum beta-lactamase (ESBL) production (11,12). Emerging antibiotic resistance is currently acknowledged as one of the most significant public health problems with high mortality rates associated with multidrug-resistant bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…In a study at a children's hospital in China, ~72% of gram-negative bacilli were found to be MDR, with ESBLs being most prevalent [72]. Other studies have demonstrated similar findings [73]. In Ethiopia, all isolates of Acinetobacter baumanni and Pseudomonas aeruginosa were resistant to three-to-six antibiotics from different classes.…”
Section: Emerging Gram-negative Resistance In Paediatricsmentioning
confidence: 82%
“…These bacteria are clinically challenging to manage and pose a serious threat to compromised patients such as preterm infants. 29 Interestingly, FMT treatment reduced levels of cefotaxime resistance after AB treatment, which warrants further investigation. On the other hand, FMT is also capable of transmitting AB resistance genes to recipients, and likely to a greater degree if the recipient microbiota is naïve or dysbiotic, emphasizing the need for rigorous screening of donor stool.…”
Section: Discussionmentioning
confidence: 95%